Sociopsychological characteristics of late nonagenarians in Japan: the protocol of the Arakawa 95+ study. Issue 1 (13th May 2019) - Niimura, Hidehito; Eguchi, Yoko; Kida, Hisashi; Suzuki, Kouta; Takayama, Midori; Mimura, Masaru
Abstract : Aim: The aim of this study was to examine sociopsychological characteristics of the oldest old in Japan. We conducted a baseline survey of a community‐based cohort of persons aged 95 or older. Methods: Participants were aged 95+ years and resided in Arakawa Ward in Tokyo on 1 January 2016. We mailed a questionnaire to these individuals to assess their physical, mental, and social status. Subsequently, if respondents agreed, we conducted in‐home interviews and examined their physical and cognitive function. Also, we mailed non‐respondents a simplified version of full questionnaire. Additionally, we examined the basic registered data of the study population and the status of their Long‐term Care Insurance. Data at baseline and 1‐year follow‐up were compared. Results: With regard to Long‐term Care Insurance, 423 residents aged 95+ years (78.0%) were on long‐term care level, 35 (6.5%) were on support level, and 84 (15.5%) did not require support. At the 1‐year follow‐up, 275 (50.7%) had the same care level, 107 (19.7%) required a greater level of care, and 131 had died (annual death rate: 24.2%). Compared to the simplified questionnaire group ( n = 128) and the full questionnaire‐only group ( n = 14), a higher proportion of respondents who had completed the full questionnaire and had in‐home interviews ( n = 26) were men, lived only with a spouse, had higher activities of daily living, and reported more positive feelings and well‐being. Conclusions: In the late nonagenarian population, the annual death rate was high, and care needs increased rapidly. However, some persons maintained the same care level or even showed improvement and successful ageing.